Literatur Riview : Pengaruh Penggunaan Media Digital Flipbook terhadap Hasil Belajar Siswa pada Mata Pelajaran IPAS bidang IPS di Sekolah Dasar. - Silvia Rahma Sari; Elfia Sukma; Inggria Kharisma (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the use of digital learning media in the form of flipbooks in improving student learning outcomes in IPAS subjects in the social studies field at the elementary school level. The method used is a literature review by examining various sources such as scientific journals, books, and relevant articles in the period 2020–2025. The results of the study show that the use of flipbooks as digital learning media can increase student interest, motivation, and understanding because of the interactive presentation of material through a combination of text, images, audio, and video. In addition, flipbooks also make it easier for students to access learning materials anytime and anywhere. Therefore, flipbooks are considered effective as digital learning media innovations in improving student learning outcomes in social studies learning.